Customers' relationship with their grocery store: Direct and moderating effects from store format and loyalty programs - Filipe, Sandra (2018)
This paper aims: (i) to characterize the priorities designed and implemented by grocery retailers concerning relationship marketing with customers; (ii) to analyse customers’ relationship with their grocery store and to evaluate store format and loyalty programs as key determinants of this relationship. Exploratory interviews were conducted with grocery store managers. Two independent samples of Portuguese customers answered a questionnaire and collected data were analysed using Structural Equation Modelling. Main results suggest that supermarkets lead to higher levels of customers’ trust (directly) and customers’ loyalty (indirectly). Furthermore, the positive effect of customers’ satisfaction on customers’ loyalty is higher for members of grocery store loyalty programs.